Retrospective cohort study investigating association between precancerous gastric lesions and colorectal neoplasm risk - Pan, Hui; Zhang, Yu-Long; Fang, Chao-Ying; Chen, Yu-Dai; He, Li-Ping; Zheng, Xiao-Ling; Li, Xiaowen (Frontiers in Oncology, 2024)
Background: Colorectal cancer (CRC) is considered the most prevalent synchronous malignancy in patients with gastric cancer. This large retrospective study aims to clarify correlations between gastric histopathology stages and risks of specific colorectal neoplasms, to optimize screening and reduce preventable CRC.: Clinical data of 36,708 patients undergoing gastroscopy and colonoscopy from 2005-2022 were retrospectively analyzed. Correlations between gastric and colorectal histopathology were assessed by multivariate analysis. Outcomes of interest included non-adenomatous polyps (NAP), conventional adenomas (CAs), serrated polyps (SPs), and CRC. Statistical analysis used R version 4.0.4.Older age (≥50 years) and Helicobacter pylori infection (HPI) were associated with increased risks of conventional adenomas (CAs), serrated polyps (SPs), non-adenomatous polyps (NAP), and colorectal cancer (CRC). Moderate to severe intestinal metaplasia specifically increased risks of NAP and CAs by 1.17-fold (95% CI 1.05-1.3) and 1.19-fold (95% CI 1.09-1.31), respectively. For CRC risk, low-grade intraepithelial neoplasia increased risk by 1.41-fold (95% CI 1.08-1.84), while high-grade intraepithelial neoplasia (OR 3.76, 95% CI 2.25-6.29) and gastric cancer (OR 4.81, 95% CI 3.25-7.09) showed strong associations. More advanced gastric pathology was correlated with progressively higher risks of CRC.Conclusions: Precancerous gastric conditions are associated with increased colorectal neoplasm risk. Our findings can inform screening guidelines to target high-risk subgroups, advancing colorectal cancer prevention and reducing disease burden.